Re-imagining bisexuality and Christianity: The negotiation of Christianity in the lives of bisexual women and men. (September 2014) - Toft, Alex
Research exploring non-heterosexual sexuality and Christianity has tended to conflate 'lesbian and gay', with 'bisexual', effacing the latter. This article explores how bisexual women and men in particular understand their Christianity, where they have been denied access to institutionalised Christianity and have re-imagined their faith. I examine how bisexuality is understood by popular Christian denominations and how respondents challenge these standpoints. The respondents reshaped their faith to be more inclusive of bisexuality and re-imagined their sexuality to fit with their religious faith. I draw upon data from 80 self-completion questionnaires and 20 in-depth interviews.